Ślady Komeńskiego we współczesności: utopijność versus realna obecność jego założeń pedagogicznych i społecznych - Dobrowolska, Barbara (Siedleckie Zeszyty Komeniologiczne seria Pedagogika, 2021)
The article is an attempt to analyze selected aspects in the pedagogical and social views of John Amos Comenius. Comparing Comenius with the present day is looking for his traces in it. At the same time, in the literature covering studies of Comenius’ output, there are categories of utopia and realism. To explain them, a short analysis of the relationship between utopia and pedagogy was undertaken. In pedagogy as a social science, a vision of a better world is always created, which is not always accepted. Comenius’ views, described as utopia, seem to be accomplished today in practice and pedagogical theory, although their actual sources are not always used.